2003
DOI: 10.1254/jphs.92.13
|View full text |Cite
|
Sign up to set email alerts
|

KR-31466, a Benzopyranylindol Analog, Attenuates Hypoxic Injury Through Mitochondrial KATP Channel and Protein Kinase C Activation in Heart-Derived H9c2 Cells

Abstract: Abstract. In the present study, we investigated whether a novel benzopyranylindol analogue, KR-31466 (KR466) (1-[(2S,3R,4S)-3,4-dihydro-2-dimethoxymethyl-3-hydroxy-2-methyl-6-nitro-2H-1-benzopyran-4-yl]-1H-indole-2-carboxylic acid ethyl ester) can attenuate hypoxic injury in heart-derived H9c2 cells and, if so, whether the protective effect of KR466 is mediated through mitochondrial ATP-sensitive potassium (mtK ATP ) opening. The treatment of H9c2 cells with KR466 (3 -30 mM) significantly reduced hypoxia-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It is believed that PIN, a cyanoguanidine derivative, exerts its cardioprotective effect primarily via the opening of sarK ATP channels (Lin et al 2004, Matar et al 2000, Saltman et al 2000. In contrast, SDZ, a benzopyran derivative, and related compounds such as KR-31378 (Moon et al 2004), KR 466 (Jung et al 2003), BMS-191095 (Fischbach et al 2004, Neckar et al 2002 and bimakalim (Eells et al 2000) have all been shown to act specifically via the opening of mitoK ATP channels, which are more relevant to preconditioning and sustained hypoxia and ischaemia of the heart. It is very possible that while the potent hyperpolarization effect of SDZ alone could be observed, its protective effect on metabolically compromised cardiomyocytes could not be seen because the present study only dealt with acute metabolic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that PIN, a cyanoguanidine derivative, exerts its cardioprotective effect primarily via the opening of sarK ATP channels (Lin et al 2004, Matar et al 2000, Saltman et al 2000. In contrast, SDZ, a benzopyran derivative, and related compounds such as KR-31378 (Moon et al 2004), KR 466 (Jung et al 2003), BMS-191095 (Fischbach et al 2004, Neckar et al 2002 and bimakalim (Eells et al 2000) have all been shown to act specifically via the opening of mitoK ATP channels, which are more relevant to preconditioning and sustained hypoxia and ischaemia of the heart. It is very possible that while the potent hyperpolarization effect of SDZ alone could be observed, its protective effect on metabolically compromised cardiomyocytes could not be seen because the present study only dealt with acute metabolic inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…To examine the extent of apoptotic cell death, we performed TUNEL‐staining after 8 and 6 h of hypoxia in H9c2 cells and neonatal rat cardiomyocytes, respectively, as described previously (Jung et al ., 2003; Kim et al ., 2005). There are three groups of diazoxide treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the benzopyranyl‐indole analog KR‐31466 reduces hypoxic injury in heart‐derived H9c2 cells through mitoK ATP opening. Jung et al suggested that this protection from hypoxia‐induced death could also involve PKC activation …”
Section: Mitokatp Channelsmentioning
confidence: 99%